What We Learned about Corporate Governance and Code Development in Sub-Saharan Africa - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
This document is a high-level account of discussions held and conclusions reached during theroadshow. It describes 10 learnings attained over the more than two decades of experience in code development in South Africa. Under each of these learnings, we present the South African experience as well as experiences shared in the various countries where the roadshow was conducted. The purpose of this document is to provide guidance to IFC staff, regulators, and private institutions (such as institutes for directors and corporate governance) for developing codes of corporate governance in Sub-Saharan African countries and potentially other developing economies. The objective is for the insights shared in this document to support achievement of the following results: a more effective process of code development, code content that will be easier for organizations to implement, a higher degree of commitment by the users of the code and good governance that will result in better outcomes for organizations as well as the communities and countries in which they operate. This guidance document should be read in conjunction with the IFC Toolkit for Developing Corporate Governance Codes of Best Practice. Before sharing the learnings, it is important to understand the context for the application of corporate governance in Africa. This will provide perspective on why some of the learnings are vital. Organizations—the users of codes of corporate governance—operate in a broader context, which King IV calls the “triple context,” consisting of the economy, society, and natural environment in which organizations operate. In Africa, depending on the country, the triple context may appear as economic and political instability, lack of or failing infrastructure, skills shortage, inequality, water and food scarcity due to environmental vulnerability, and corruption. Furthermore, the application of corporate governance is not mature in all African countries. An IFC study on the link between governance and corporate performance examined the degree of African firms’ adherence to certain aspects of corporate governance. If those foundations are weak, it is unlikely that other areas of corporate governance could be strong. However, it is encouraging that, taken together, the firms scored above 50 percent on all five of the dimensions assessed. Organizations in Africa operate in a challenging triple context, and much work must be done to gain maturity in the corporate governance practices they follow. Codes for corporate governance should be cognizant of these realities.